Mediating Role of Green Trust in the Link Between Green Perceived Value, Risk, and Purchase Intention of Electric Motorcycles - Cahya, Nur; Santi Paramita, Veronika (Yayasan Sinergi Kawula Muda, 2025)
This study aims to examine the influence of green perceived risk (GPR) and green perceived value (GPV) on purchase intention (PI) through green trust (GT) in Honda EM-1 electric motorcycles. A total of 271 respondents were selected using the Lemeshow method. Data was collected through a cross-sectional or one-shot research approach. The research instrument successfully passed validity and reliability tests. Structural equation modelling (SEM) was employed for data analysis using Smart-PLS version 3.0. The study used PLS software, including outer and inner model assessments. The outer model analysis evaluates convergent validity, discriminant validity, and composite reliability, while the inner model analysis includes r-square, f-square, model fit tests, path analysis, and hypothesis testing. Among the four proposed hypotheses, all were found to have a significant effect. Green perceived value (GPV) positively influences purchase intention (PI), both directly and indirectly, through green trust (GT). Conversely, green perceived risk (GPR) negatively affects purchase intention (PI), both directly and indirectly, through green trust (GT).